The Emergence of Opportunistic Products Amidst a Global Pandemic - Andrews Adugudaa Akolaa; John Paul Kosiba (ZBW – Leibniz Information Centre for Economics, 2020)
A review of online news items shows that the emergence of the COVID – 19 pandemic has driven firms to rethink strategies by re-fitting their operations to ensure survival and business sustainability whilst they support the global need to contain the pandemic. Firm resources are thus moved from current industry operations to ensure that they produce products required in a Covid-19 world and in similar worlds in the future. This article argues `opportunistic product' although now part of the organisation's product mix is distinct and novel from existing products in the firm's portfolio and must be given academic discourse in its marketing and management during and post the Covid-19 pandemic. These goods or services developed on the back of a special phenomenon especially in an emergency or disaster such as Covid-19 to solve immediate needs of society, require firms to shift operational resources; financial, human and operational from their normal production lines into new industries. The product development process is fast-track, the product characteristics are unique and the motives differ from the normal firm products, Therefore, managers must know the strategic motives behind developing such products, learn how to manage, and sustain such products into the future. This paper provides an initial discussion aimed at attracting contributions across academia and industry to understand the motives of the producers, the characteristics, the management, and the behavioural aspects of these emerging products and industry practice in order since they are distinct to inform future directions for opportunistic products as a novel concept.
Keywords: F41; 330; Products; Covid-19; Pandemic; Opportunistic; innovation